Integrating livestock climate adaptation and peacebuilding: The Climate Security Sensitivity Tool for Livestock Systems (CSSTxLS) - Sarzana, Carolina; Singh, Radhika; Meddings, George; Belli, Anna; Chepngetich, Brenda; Sagliocco, Livia; Mutheu, Mary; Pacillo, Grazia (2024)
Climate change presents profound challenges for livestock-dependent communities, particularly in fragile and conflict-affected regions where environmental, social, and political pressures intersect. The Climate Security Sensitivity Tool for Livestock Systems (CSSTxLS) builds upon the Climate Security Sensitivity Tool (CSST) framework to provide a specialized approach for designing conflict-sensitive and peace-responsive climate adaptation interventions tailored to livestock systems. This working paper outlines the development and application of the CSSTxLS framework, which was shaped by the results of a collaborative workshop held in October 2024 at the International Livestock Research Institute (ILRI) campus in Nairobi, Kenya. The workshop brought together experts in climate adaptation, conflict resolution, and livestock systems to contextualize the CSST framework for livestock-based livelihoods. Using case studies from Turkana and Mandera counties in Kenya, the paper explores the interactions between conflict drivers – such as weak infrastructure, socio-economic vulnerabilities, and human hazards – and climate-peace mechanisms, including economic development, institutional strengthening, resource sustainability, trust-building, and resilience enhancement. It highlights the importance of local context and expert validation in designing effective interventions. Drawing on the workshop findings and broader literature on pastoralist livelihood transitions, this paper demonstrates how climate adaptation can mitigate conflict risks, enhance resilience, and foster peace. By integrating traditional knowledge, addressing power asymmetries, and prioritizing equitable resource distribution, the CSSTxLS provides a pathway for adaptive strategies that address climate challenges while contributing to sustainable peacebuilding in vulnerable regions.